On commutativity theorems for rings - H. A. S. Abujabal (International Journal of Mathematics and Mathematical Sciences, 1990)
Let R be an associative ring with unity. It is proved that if R satisfies the polynomial identity [xny−ymxn,x]=0(m>1,n≥1), then R is commutative. Two or more related results are also obtained.